The Role Of Communication In Improving The Quality Of Islamic Religious Education Learning In The Modern Education Era - Bushaeri, Nur Muhammad; Ahmad Fathurrohman, Asep; Syafi'e, Rachmat; Saepudin, Dindin (JURNAL PENDIDIKAN ISLAM AL I’TIBAR, 2024)
This article discusses the crucial role of communication in improving the quality of learning in the modern education era. With the development of technology and changes in learning paradigms, communication is not only a means of delivering information, but also as the main foundation in shaping effective and continuous learning experiences. Through deep insights, this article explores how communication facilitates collaborative learning, overcomes the constraints of space and time, and forms essential interpersonal skills. Communication is also key in accommodating cultural diversity and ensuring parental involvement in learning. By understanding the role of this communication, this article invites to design innovative learning methods, create an inclusive environment, and prepare students for future demands. Through a holistic approach to communication in the context of modern education, this article summarizes concepts and strategies that can be applied to improve the quality of learning and ensure the relevance of education to the dynamics of the times